2012
DOI: 10.1093/annonc/mdr585
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a cancer clinical trials web site on discussions about trial participation: a cluster randomized trial

Abstract: Good communication between patients and physicians is essential. Within this context, a web site such as Australian Cancer Trials may be an important tool to encourage discussion about clinical trial participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Thus, the illness type and stage of included patients appears particularly heterogeneous. Because of the aims and scope of the two primary studies from which the audio tapes were derived , the FM's relationship to the patient was able to be determined in only 59 out of the 72 consultations (Table ). Spouse/partners most often attended (wife 38%; husband 34%), followed by daughters (15%) then sisters (7%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the illness type and stage of included patients appears particularly heterogeneous. Because of the aims and scope of the two primary studies from which the audio tapes were derived , the FM's relationship to the patient was able to be determined in only 59 out of the 72 consultations (Table ). Spouse/partners most often attended (wife 38%; husband 34%), followed by daughters (15%) then sisters (7%).…”
Section: Resultsmentioning
confidence: 99%
“…Transcripts of audiotaped initial medical or radiation oncology consultations collected for two previous studies reported elsewhere were analysed using KINcode. We selected transcripts of adult cancer patients (any age, gender, cancer type or stage) who were accompanied by an adult ‘FM’ (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decision aids may increase patients´ perception of the desease but it is not guaranteed that they lead to an increase of shared decision making [42]. Last but not least, the possibility of free online access to information about studies such as the ´Australian Cancer Trials´ [43] helps to optimise the information basis for patients, family members and physicians.…”
Section: Discussionmentioning
confidence: 99%
“…28 Furthermore, even in the absence of language barriers, explaining and understanding the concepts, including randomization, have been shown to pose a unique challenge in many instances. 30 For glioma patients, cognitive and behavioral changes may impact not only study eligibility but may also potentially impact the complex process of informed consent. 31 In a prospective study investigating longitudinal changes in decisional capacity, Marson et al demonstrated that patients with malignant gliomas had significant impairment of their capacity to consent to medical treatment and, most importantly, to consent to research participation.…”
Section: Recruitment Barriersmentioning
confidence: 99%